Performance Analysis of Forest Management Unit Region III Kisaran, North Sumatra Province - Oktavia, Ade; Bejo Slamet; OK Hasnanda Syahputra (Journal of Sylva Indonesiana, 2024)
Forest Management Units (FMU) are a form of forestry policy that has become a key instrument in reforming Indonesia's forestry industry. North Sumatra Province has 33 FMU units, comprising 15 Production FMUs and 18 Protection FMUs, all grouped into 16 FMU Regions. This study evaluates forest management performance in the FMU Region III Kisaran. The performance assessment used the Forest Watch Indonesia 2.0 (FWI 2.0) instrument and the Technical Guidelines for Assessing the Effectiveness of Forest Area Management from the Ministry of Environment and Forestry. The FWI 2.0 method is oriented towards performance results, benefits, and impacts. The technical guidelines for assessing the effectiveness of FMU organizations are already oriented toward the results, benefits, and impacts of forest management. Both methods used show that the performance of FMU Region III Kisaran is in the medium category. This research indicates that the selection of FMU performance assessment methods should be tailored to the purpose of the assessment